Expression of microRNAs miR21, miR146a, and miR155 in tuberous sclerosis complex cortical tubers and their regulation in human astrocytes and SEGA‐derived cell cultures. Issue 6 (25th March 2016) - van Scheppingen, J.; Iyer, A. M.; Prabowo, A. S.; Mühlebner, A.; Anink, J. J.; Scholl, T.; Feucht, M.; Jansen, F. E.; Spliet, W. G.; Krsek, P.; Zamecnik, J.; Buccoliero, A. M.; et al.
Abstract : Tuberous sclerosis complex (TSC) is a genetic disease presenting with multiple neurological symptoms including epilepsy, mental retardation, and autism. Abnormal activation of various inflammatory pathways has been observed in astrocytes in brain lesions associated with TSC. Increasing evidence supports the involvement of microRNAs in the regulation of astrocyte‐mediated inflammatory response. To study the role of inflammation‐related microRNAs in TSC, we employed real‐time PCR and in situ hybridization to characterize the expression of miR21, miR146a, and miR155 in TSC lesions (cortical tubers and subependymal giant cell astrocytomas, SEGAs). We observed an increased expression of miR21, miR146a, and miR155 in TSC tubers compared with control and perituberal brain tissue. Expression was localized in dysmorphic neurons, giant cells, and reactive astrocytes and positively correlated with IL‐1β expression. In addition, cultured human astrocytes and SEGA‐derived cell cultures were used to study the regulation of the expression of these miRNAs in response to the proinflammatory cytokine IL‐1β and to evaluate the effects of overexpression or knockdown of miR21, miR146a, and miR155 on inflammatory signaling. IL‐1β stimulation of cultured glial cells strongly induced intracellular miR21, miR146a, and miR155 expression, as well as miR146a extracellular release. IL‐1β signaling was differentially modulated by overexpression of miR155 or miR146a, which resulted in pro‐ or anti‐inflammatory effects, respectively. This study provides supportive evidence that inflammation‐related microRNAs play a role in TSC. In particular, miR146a and miR155 appear to be key players in the regulation of astrocyte‐mediated inflammatory response, with miR146a as most interesting anti‐inflammatory therapeutic candidate. GLIA 2016;64:1066–1082 Main Points: Astrocytes represent a major source and target of inflammation‐related miRNAs up‐regulated in TSC brain. miR146a and miR155 are key players in the regulation of astrocyte‐mediated inflammatory response.